THE HATHA YOGA EXERCISES TO INCREASE CARDIOVASCULAR ENDURANCE OF FEMALE STUDENT AGE 16 – 18 YEARS IN SMA NEGERI 3 DENPASAR - Laksmi, I Gusti Ayu Dwita Wahyu; Dewi, Anak Ayu Nyoman Trisna Narta; Sugiritama, I Wayan (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 2 (2018): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2018.v06.i02.p05, 2018)
ABSTRACT Cardiovascular endurance is the ability to perform an activity with a long time without experiencing fatigue. The purpose of this research is to know the effect of the increase in the hatha yoga exercise in improving cardiovascular endurance. This research is experimental research using the design of One Group Pre Test and Post Test Design. Sampling techniques in this research is consecutive sampling. Sample research totalling sixteen people given hatha yoga exercise. The exercises were done for 12 weeks with frequency of three times a week in SMA Negeri 3 Denpasar. Data collection is done by measuring cardiovascular endurance by using the cooper 2,4 kilometers test before and after the training. The result using Paired Sample T-test obtainable results showed p = 0,000 < 0,05, so it can be concluded that hatha yoga exercises in increasing cardiovascular endurance. Keyword: Cardiovascular Endurance, Hatha Yoga Exercises, Female Student